Â¿Los Millennials Saltillenses Son Innovadores Como Consumidores de Ropa? - Wong, Adriana MÃ©ndez; Ruiz, Edith Reyes; Siller, JesÃºs Francisco Mellado; RamÃrez, Karina Lizbeth RodrÃguez (European Scientific Journal, ESJ, 2017)
The objective of this research work is to analyze the behavior of young people belonging to generation Y known as millennials, regarding the purchase of clothing. According to Kotler and Keller (2012), a generation is a group of persons whose ages are similar and who lived in the same era. This study is considered as a descriptive and exploratory investigation. It is based on a sample of 261 persons from 21 to 36 years of age in the city of Saltillo, Coahuila. A questionnaire was applied with the scale ’Type of consumers of clothes of Chengedzai’ according to the study of Manillall and Lawrence (2014). Using Pearson’s chi square and an answer percentage comparison with the IBM SPSS software, the findings suggest that with regard to the innovative factor, the interviewees do not consider themselves as an innovative buyer when they buy clothes. This is because the answers concerning the variables that suggest this have a low score.